Levels Of Income And Welfare Enjoyed By Palm Oil Crafters - Siti Asiah Jamil; Suci Adhis Rahmadani; M. Ridwan; Mulono Apriyanto (Akademi Komunitas Perkebunan Yogyakarta, 2023)
This study examined the income and welfare of palm oil farmers in Kempas Village, Kempas District, Indragiri Hilir Regency. The research sample consisted of forty individuals and the income was broken down into on-farm income, off-farm revenue, and non-farm income, while household costs were broken down into food expenditure and non-food expenditure. The results showed that the average income was Rp. 101,344,806 per year, the level of welfare was high (57.5%) and medium (42.5%), and the number of palm oil farmers living in poverty was low.